2009
DOI: 10.1152/ajpregu.00039.2009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ih, but not inhibition of IM, is a key mechanism underlying the PACAP-induced increase in excitability of guinea pig intrinsic cardiac neurons

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) increases excitability of guinea pig cardiac neurons, an effect mediated by PACAP-selective PAC(1) receptors. In dissociated guinea pig cardiac neurons, PACAP causes a positive shift of the voltage dependence of activation of the hyperpolarization-activated nonselective cation current (I(h)). This observation suggested that an enhancement of I(h) contributed to the increase in excitability in neurons within whole-mount cardiac ganglia preparations. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Thus, it is imperative to understand what ionic conductances regulate cardiac neuron excitability. Evidence presented previously indicated that a PACAP-enhanced I h was one mechanism contributing to the PACAP-induced increase in cardiac neuron excitability (36,51). A PACAP-induced calcium influx also was found to be a critical step in the peptide modulation of excitability (50).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, it is imperative to understand what ionic conductances regulate cardiac neuron excitability. Evidence presented previously indicated that a PACAP-enhanced I h was one mechanism contributing to the PACAP-induced increase in cardiac neuron excitability (36,51). A PACAP-induced calcium influx also was found to be a critical step in the peptide modulation of excitability (50).…”
Section: Discussionmentioning
confidence: 84%
“…2A). This rectification or "sag" in the hyperpolarizing response is due to the activation of I h , the inward current flowing through a hyperpolarization-activated nonselective cationic conductance (HCN) (10,15,36,51,55). Following termination of the hyperpolarization, a hyperpolarization-induced rebound depolarization often occurs (Fig.…”
Section: Ni 2ϩ Suppresses the Pacap-induced Increase In Excitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For intracellular recording, atrial whole mount preparations were pinned in a Sylgard-lined chamber and superfused continuously (6–7 ml/min) with Kreb’s solution also containing 10 mM HEPES buffer (Braas et al 1998; Tompkins et al 2006, 2007, 2009; Tompkins and Parsons 2008). The experiments were done with the bathing solution maintained between 32–35°C.…”
Section: Methodsmentioning
confidence: 99%
“…The PAC1 receptor can also modulate the activity of phospholipase D (PLD) in recombinant cell lines through a small G protein independent of the PLC-PKC pathway (30). Once activated, these pathways do the bidding of PACAP by changing gene expression, releasing Ca 2ϩ from internal stores, and/or activating/phosphorylating a range of ion channels including T-type Ca 2ϩ channels (8,19,38,55,57,58). The cellular mechanisms by which PACAP leads to secretion have been particularly well studied in the rat PC12 cell line, which shares the oxygen sensing and catecholaminergic phenotype of carotid body glomus cells (68).…”
mentioning
confidence: 99%